Urinary Tract Infections in Elderly Patients: A 10-Year Study on Their Epidemiology and Antibiotic Resistance Based on the WHO Access, Watch, Reserve (AWaRe) Classification - Márió Gajdács; Marianna Ábrók; Andrea Lázár; Katalin Burián (MDPI AG, 2021)
The ageing of the population-especially in developed countries-has brought on many societal challenges and has significantly contributed to the burden on healthcare infrastructures worldwide. Elderly persons (aged ≥ 65 years) are at higher risk for developing UTIs, due to a range of intrinsic and extrinsic risk factors, and they often delay seeking treatment. A retrospective observational study was performed regarding the epidemiology and resistance of UTIs in elderly patients. Identification of the isolates was carried out using VITEK 2 ID/AST and MALDI-TOF mass spectrometry. Antibiotic resistance in these isolates was assessed based on EUCAST guidelines, and were grouped into the WHO AWaRe (Access, Watch, Reserve) classification of antimicrobials. During the 10-year study period, n = 4214 (421.4 ± 118.7/year) and n = 4952 (495.2 ± 274.6) laboratory-confirmed UTIs were recorded in inpatients and outpatients, respectively. The causative agents showed differentiation among outpatients and inpatients: Escherichia coli (48.14% vs. 25.65%; p = 0.001), Enterococcus spp. (20.15% vs. 21.52%; p > 0.05), Klebsiella spp. (16.28% vs. 16.26%; p > 0.05), Pseudomonas spp. (4.40%vs. 13.36%; p = 0.001); Proteus-Providencia-Morganella group (4.56% vs. 10.96%; p = 0.001); Candida spp. (0.53% vs. 5.98%; p = 0.001); Citrobacter-Enterobacter-Serratia group (1.90% vs. 2.71%; p < 0.05). Significantly higher resistance rates were observed in inpatient isolates for many Access and Watch antibiotics compared to isolates of outpatient origin; in addition, resistance rates were higher in these uropathogens compared to the previously recorded rates in the region. More care should be taken for the diagnosis and treatment of UTIs affecting elderly patients, as they represent a particularly vulnerable patient population.